Field notes contributed by Thomas J. Staudt, spring 1980 - Staudt, Thomas J.et al (1980)
List of birds and locations contributed by Thomas J. Staudt with observers Marilyn Smith Glasson and Carl J. Bendorf. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed